INVOLVEMENT OF CHILDREN IN ROAD TRAFFIC ACCIDENTS IN EASTERN NEPAL (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
An accident has been defined as an unexpected unplanned occurrence which may involve injury (Howgarth 1978). Accidents  represents a major epidemic of non-communicable disease in the present century (Park 2000). Since the advent of vehicles, the  number of road traffic aciddent has risen proportionate to the number of vehicles manufactured. In many countries, motor vehicles accidents, rank first among all fatal accidents. There are almost 885,000 deaths from RTA annually in the world (WHO  1995). In addition, RTA provide some 10% or more of the average forensic autopsy load (Mason). The term killed (in an RTA) is  defined as any person who was killed outright or who died within 30 days as a result of accident (WHO 1984). In a country like  ours, with poor roads, ill-managed vehicles, improper rash driving, highway being the sites for play of children and inadequate  teaching of traffic rules to drivers as well as its inadequate incorporation in school curriculum leads to increased involvement children in RTA.
Keywords: Majority; Bernard Knight